Submit your agony: uma leitura biopolítica da plataforma digital Beautiful Agony - Pereira, Camila Boarini (2019)
This research examines the testimony and exposure of masturbatory orgasming on the digital platform Beautiful Agony. The site, launched in 2013, has a paid collection, which contains more than four thousand videos that portray people masturbating until they orgasm. The films have a frame on the face, with no scenes of body nudity. The site also includes videos of "confessions", which present the participants' reports describing the sensations experienced and what they imagined in the moment of orgasming. The platform belongs to an Australian company called FECK, which has four other projects, and refuses the classification of pornography. The goal is to investigate whether and how these sites differ from what is available in the digital environment, and reflect whether they actually distance themselves from the pornographic industry. The hypothesis is that the new technological panorama and its imperatives of visibility and hyperexposure of bodies and their intimacies, characteristic of social networks, produce new subjectivities, also guided by neoliberal rationality, in its cult of visibility and transparency. Authors such as Foucault (2014), Sibilia (2016), Dufour (2013), Preciado (2008), Bauman (2008) and Dardot and Laval (2016) will be summoned to produce a biopolitical reading of the institutional discourse and videos presented. The methodology includes bibliographical review and case study. Beyond identifying that it is necessary to bring the reflection to a wider public than the one that consumes and produces this type of information, the project is justified by the urgency to advance in the studies on the impacts of the dissolution of the previously established borders between the public and private